APLIKASI UNTUK PEMBUATAN DAN MEMUTAR MATRIKS KUBUS TIGA DIMENSI MEMANFAATKAN MICROSOFT VB.NET - Yulina; Septi Wulandari (LPPM Universitas Muhammadiyah Kotabumi, 2020)
The use of computers in almost all areas of activity is to assist in solving various problems. In mathematics computer programs can also be used to calculate problems that already have a fixed formula. In this case, a computer program is used to create a 3-dimensional cube matrix with different segment sizes and can be rotated as needed and will obtain the main diagonal length of the cube.